PEMBUATAN SILICA THIN FILM SEBAGAI PELAPIS MEMBRAN DARI PREKURSOR TEOS (TETRA ETHYL ORTOSILICATE) - Muthia Elma (Universitas Lambung Mangkurat, 2017)
Abstract. Membrane layer ia a semipermeable material that serves as a separator based on its physical properties. One type of this material is a silica-based membrane that offers higher selectivity in the desalination process of water. However, this membrane also has a weakness in hydro-stability that will ultimately affect the final desalination water results. The aim of this research is to know silica gel fabrication using sol-gel process and under various pH from 1 to 9. The precursorused was TEOS which is then applied as a layer on top of membrane support for water desalination process. The method was employed TEOS as a precursor, ethanol, HNO3 and NH3 with a two-step acid-base catalysed sol gel process method at 500C for 3 hours. In order to characterize this thinnfilm, the silica sil was dried at 600C for 2 hours and characterized using FTIR. It was found that there are several peaks at wavelength 1084, 962 and 800 cm-1 on sol-gel with pH 6. Siloxane groups can be seen at wavelengths 1084 cm-1 and 800 cm-1 while silanol group at peak 962 cm-1. Thus, the silica thin film membrane pH 6 shows a tendency to form a good micro and mesoporous material applied in separating salt content in the feed solution compared to the other sols.Keywords: membrane, silica sol, TEOS, xerogel